Edukasi Gizi Seimbang pada Bayi dan Balita untuk Pencegahan Stunting di RW 08 Desa Babakan Kecamatan Ciseeng - Nina Yusnia; Azzahra Herlyana; Salma Azzahra (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
According to the World Health Organization (WHO), in 2023 there will be 49 million children under five who will experience malnutrition and almost 17 million children under five will experience malnutrition and the combined estimate of child malnutrition (JME) (UNICEF-WHO-WB) In 2022, there will be 148.1 million children under the age of 5 experience (stunting). The aim of this Community Midwifery Care intervention practice is to provide education to increase knowledge about balanced nutrition for infants and toddlers to prevent stunting in Rw 08 Babagan Village. The method used is lecture. The participants included pregnant women, mothers with babies and toddlers, 32 couples of childbearing age. The results of this midwifery care intervention activity showed that there was a significant influence on balanced nutrition education for babies and toddlers as evidenced by the pre-test scores which showed that the number of people who had poor knowledge was 23 respondents (71.9%) and the post-test results showed the number of people who had 24 respondents (75.0%) had good knowledge. The conclusion: that the health problem in Rw 08 is related to the low knowledge of mothers who have babies and toddlers regarding balanced nutrition.